Pharmacokinetics of Cephalexin after Intravenous and Single and Multiple Intramuscular Administration to Rabbit - Meneses, María Laura (2013)
Cephalexin is a first generation cephalosporin widely used in rabbits. Its spectrum includes Pasteurella multocida and Staphylococcus aureus. These bacteria, together with Bordetella bronchiseptica, are the main cause of respiratory infections. Although many textbooks on rabbit therapeutics report the use of cephalexin, including administration schedules, there are not published papers on the pharmacokinetics of cephalexin after IV and IM administration to rabbit. Therefore, the objective of the present study was to describe cephalexin disposition in rabbits after intravenous and single and multiple intramuscular administrations. Three administration schedules were studied: single IV administration (10 mg/kg), single IM administration (10 mg/kg) and multiple IM administration (2.5 mg/kg/6). Serial blood samples were collected over a 24 h period. Cephalexin plasma concentrations were determined by microbiological method using Kocuria rhizophila ATCC 9341 as microorganism test. No statistical differences were observed between routes of administration for any of the estimated PK parameters. The unique difference was observed on bioavailability between intramuscular administration schedules. Elimination half-life was 1.45, 1.09 and 1.91 h for the single IV, single IM and multiple IM administration, respectively. Bioavailability after single and multiple IM administration was 47 and 97.5%, respectively. After multiple IM administration maximum and minimum plasma concentration at steady state were 2.77 and 0.34 µg/ml, while Cmax after single IM administration was 9. 22 µg/ml. Considering that for betalactams the PK/PD breakpoint recommended for efficacy (T > MIC) should be 50–80% and that the reported MIC for most gram-positive organisms and Pasteurella multocida is ≤1.0 μg/ml, the present study demonstrates that a single IM dose of 10 mg/kg/24 h is enough to maintain therapeutic concentrations for a 24 hours period. When a 2.5mg/kg dose is used administration every 6 hours is recommended.